The World book encyclopedia. - Field Enterprises Educational Corporation (Chicago : Field Enterprises Educational Corp., 1977)
An encyclopedia designed especially to meet the needs of elementary, junior high, and high school students.
Australasia supplement (2 v.) and British Isles supplement (2 v.) are each numbered as v. 23-24.
Includes bibliographies and index.
Keywords: Encyclopedias and dictionaries